2021
DOI: 10.1186/s12873-021-00493-5
|View full text |Cite
|
Sign up to set email alerts
|

Live video from bystanders’ smartphones to medical dispatchers in real emergencies

Abstract: Background Medical dispatchers have limited information to assess the appropriate emergency response when citizens call the emergency number. We explored whether live video from bystanders’ smartphones changed emergency response and was beneficial for the dispatcher and caller. Methods From June 2019 to February 2020, all medical dispatchers could add live video to the emergency calls at Copenhagen Emergency Medical Services, Denmark. Live video wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 27 publications
3
75
0
Order By: Relevance
“…Further details about the implementation can be found in another study. 14 The audio and video recording were combined for the analysis. All suspected OCHA cases where CPR continued or started after the live video transmission had begun were included.…”
Section: Data Collection and Outcomementioning
confidence: 99%
“…Further details about the implementation can be found in another study. 14 The audio and video recording were combined for the analysis. All suspected OCHA cases where CPR continued or started after the live video transmission had begun were included.…”
Section: Data Collection and Outcomementioning
confidence: 99%
“…23 After conducting patients' medical condition and history assessment, physical examination with vital sign monitoring, and other diagnostic procedures, EMS paramedics can either tele-transmit the result to a physician and get notified with text or audio for further advice for diagnosis or therapy 24 , or use audio and video features where they can connect virtually to physicians. [16][17][18][19]22,24,25,27 Catapan et al 33 found that video teleconsultation has numerous benefits. A few of the benefits are the ability to diagnose accurately, similar to face-to-face, the ability to deliver care without moving the patient, and the ability to adapt to current time constraints for health care.…”
Section: Discussionmentioning
confidence: 99%
“…34 EMS quality for pre-hospital care is also determined by how they respond to emergency calls from people who have experienced a medical emergency. 35 GoodSAM, a telemedicine-based application proposed by Linderoth et al 18 , connected EMS and bystanders using live videos. A 38.2% improvement in the paramedics' assessment occurred after the live videos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations